11β-Hydroxysteroid Dehydrogenase Type 1 Gene Knockout Attenuates Atherosclerosis and In Vivo Foam Cell Formation in Hyperlipidemic apoE−/− Mice - García, Ricardo A.; Search, Debra J.; Lupisella, John A.; Ostrowski, Jacek; Guan, Bo; Chen, Jian; Yang, Wen-Pin; Truong, Amy; He, Aiqing; Zhang, Rongan; Yan, Mujing; Hellings, Samuel E.; et al. (PLOS ONE, 2013)
Background Chronic glucocorticoid excess has been linked to increased atherosclerosis and general cardiovascular risk in humans. The enzyme 11β-hydroxysteroid dehydrogenase type 1 (11βHSD1) increases active glucocorticoid levels within tissues by catalyzing the conversion of cortisone to cortisol. Pharmacological inhibition of 11βHSD1 has been shown to reduce atherosclerosis in murine models. However, the cellular and molecular details for this effect have not been elucidated. Methodology/Principal Findings To examine the role of 11βHSD1 in atherogenesis, 11βHSD1 knockout mice were created on the pro-atherogenic apoE−/− background. Following 14 weeks of Western diet, aortic cholesterol levels were reduced 50% in 11βHSD1−/−/apoE−/− mice vs. 11βHSD1+/+/apoE−/− mice without changes in plasma cholesterol. Aortic 7-ketocholesterol content was reduced 40% in 11βHSD1−/−/apoE−/− mice vs. control. In the aortic root, plaque size, necrotic core area and macrophage content were reduced ∼30% in 11βHSD1−/−/apoE−/− mice. Bone marrow transplantation from 11βHSD1−/−/apoE−/− mice into apoE−/− recipients reduced plaque area 39–46% in the thoracic aorta. In vivo foam cell formation was evaluated in thioglycollate-elicited peritoneal macrophages from 11βHSD1+/+/apoE−/− and 11βHSD1−/−/apoE−/− mice fed a Western diet for ∼5 weeks. Foam cell cholesterol levels were reduced 48% in 11βHSD1−/−/apoE−/− mice vs. control. Microarray profiling of peritoneal macrophages revealed differential expression of genes involved in inflammation, stress response and energy metabolism. Several toll-like receptors (TLRs) were downregulated in 11βHSD1−/−/apoE−/− mice including TLR 1, 3 and 4. Cytokine release from 11βHSD1−/−/apoE−/−-derived peritoneal foam cells was attenuated following challenge with oxidized LDL. Conclusions These findings suggest that 11βHSD1 inhibition may have the potential to limit plaque development at the vessel wall and regulate foam cell formation independent of changes in plasma lipids. The diminished cytokine response to oxidized LDL stimulation is consistent with the reduction in TLR expression and suggests involvement of 11βHSD1 in modulating binding of pro-atherogenic TLR ligands.